2015
DOI: 10.1186/s13634-015-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive filters: stable but divergent

Abstract: The pros and cons of a quadratic error measure in the context of various applications have often been discussed. In this tutorial, we argue that it is not only a suboptimal but definitely the wrong choice when describing the stability behavior of adaptive filters. We take a walk through the past and recent history of adaptive filters and present 14 canonical forms of adaptive algorithms and even more variants thereof contrasting their mean-square with their l 2 −stability conditions. In particular, in safety c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
5
0
1
Order By: Relevance
“…where 0 ) ) 2 *+, ⁄ , and & = 3/; *+, is the maximum value of the auto correlation matrix of input x(k) and / is the standard deviation of the error signal. One of the adaptive IIR filtering LMS algorithms that has been found to be relatively stable and simple to implement is the Feintuch's LMS algorithm (Rupp, 2015;Stewart, 2006). The adaptive filter based on this algorithm is easily implemented using an IIR filter realization based on two transversal FIR filters as illustrated in Figure 1.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…where 0 ) ) 2 *+, ⁄ , and & = 3/; *+, is the maximum value of the auto correlation matrix of input x(k) and / is the standard deviation of the error signal. One of the adaptive IIR filtering LMS algorithms that has been found to be relatively stable and simple to implement is the Feintuch's LMS algorithm (Rupp, 2015;Stewart, 2006). The adaptive filter based on this algorithm is easily implemented using an IIR filter realization based on two transversal FIR filters as illustrated in Figure 1.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…An adaptive filter is a filter that self-adjusts its transfer function according to requirements, in our case, the load. However, such techniques are generally computationally expensive and sometimes, cause non-converging [20]. In our work, a simplified adaptive digital LPF structure is proposed that is guaranteed to converge and is practical to implement.…”
Section: B Algorithm Developmentmentioning
confidence: 99%
“…At the same time, it was shown that the recursive leastsquares (RLS) filter can be derived by relaxing the same criterion. Moreover, the H ∞ approach led to a so-called energy-conservation law, which has been extensively used to analyze the robustness of various kinds of adaptive filters (e.g., [2][3][4]). Thus, it established a unified framework for understanding the fundamental properties of adaptive filters [5,6].…”
Section: Introductionmentioning
confidence: 99%